Improving Functional Status of Older Adults Through Health Literacy Media: A Systematic Review - Tandilangi, Trisnawati Paulus; Rekawati, Etty; Eriska, Winda (Universitas Muhammadiyah Surakarta, 2024)
Older age can be followed by an aging process that shows a decrease in physical function due to various degenerative problems that reduce immunity caused the older adults vulnerable to infectious diseases. Health literacy can improve the physical function of the older adults in using self management agents, social support, access to health services and increasing the quality of life of older adults. The aim of this paper is to obtain the existence evidence of health literacy impact in improving older adults health status and functional or physical well-being living in community-setting and clinical setting. This paper used some databases Proquest database, PubMed, Sage Journal, Scopus, Ebscohost, Science Direct, anf Taylor & Francis. There are 11 articles published between 2014 - 2024 were reviewed using the PRISMA method. This review found that there are different types of health literacy media (print and digital) and there are combination of health literacy with physical activity interventions to deliver health information to older people. Standardized health literacy media in readability, and easy to use such as video/web/electronic, game-based, digital, and mobile-based and health literacy interventions combined with planned physical activities can increase knowledge, self-efficacy, cognitive function, quality of life, and reducing frailty score, fall risk, depression score.